The taxonomic status of two Telmatobius frog species (Anura: Telmatobiidae) from the western Andean slopes of northernmost Chile - Fibla, Pablo; Sáez, Paola A.; Salinas, Hugo; Araya, Carolina; Sallaberry, Michel; Méndez, Marco A. (Zootaxa, 2017)
On the basis of molecular and morphological evidence, we evaluated the taxonomic identity of two species of Andean frogs of the genus Telmatobius: Telmatobius pefauri and T. zapahuirensis, present in the western Andean slopes at the northern extreme of Chile. We also investigated the taxonomic assignment of five populations of Telmatobius recently discovered around the type localities of these two species. The results indicate that T. pefauri inhabits, not only Murmuntani its type locality, but also the montane localities of Belén, Copaquilla, Lupica, Saxamar and Socoroma. Our study also shows that T. pefauri and T. zapahuirensis are the same taxon. Therefore, Telmatobius zapahuirensis Veloso, Sallaberry, Navarro, Iturra, Valencia, Penna & Díaz, 1982 would be a subjective junior synonym of Telmatobius pefauri Veloso & Trueb, 1976.